Aplikasi Pupuk Organik Cair Limbah Rumah Tangga terhadap Pertumbuhan dan Hasil Tanaman Pakcoy - Mayun, Ida Ayu; Astiningsih, A.A. Made; Sumarniasih, Made Sri (Fakultas Pertanian Universitas Udayana, 2024)
Application of Household Waste Liquid Organic Fertilizer on the Growth and Yield of Pakcoy Plants. Providing nutrients to cultivated plants is very important to support plant growth and development. The aim of the research was to determine the effect of household waste liquid organic fertilizer on the growth and yield of pak choy plants and which liquid organic fertilizer gave the best results. The research was carried out in a greenhouse using a completely randomized, non-factorial design. The research used polybags filled with 10 kg of soil as a medium and planted with pak choy vegetable plants. There are three treatments used, namely liquid organic fertilizer derived from rice washing water (POCB), onion skin washing water (POCBM), and fermented fruit residues (ecoenzymes) (POCEE). There were three treatments, namely: no treatment, giving 100 ml/1 liter of water, and giving 200 ml/1 liter of water. The number of treatments was 9 and repeated 4 times, so there were 36 treatments, and 2 plants were planted in each treatment, a total of 72 plants. Maintenance includes watering, cleaning plant media, and spraying using vegetable herbicides. The parameters observed were plant height, number of leaves, and fresh weight. Observations were made two weeks after planting, and then once a week until 45 days old (harvest). Based on the research results, the treatment that provides the best growth is ecoenzyme. The highest plant height was with the ecoenzyme treatment of 200 ml/1 liter of water (POEE2), followed by POBM2, POB2, namely 18.16 cm; 16.98 cm and 16.84 cm, the number of leaves is 9.6 pieces; 9.4 strands and 9.6 strands, and fresh weight 20 g; 19.5 g and 18.9 g. The results of the research are a recommendation that household waste is useful for making liquid organic fertilizer, as shown by the growth and fresh weight yield of pak choy plants.